Obtenção de scoby de celulose bacteriana a partir de subprodutos de frutas e aplicação em SMOOTHIE - Cruz, Rafael Souza (2023)
The purpose of this research was to develop bacterial cellulose powders (SCOBY) from the fermentation of kombucha with by-products of tropical fruits, such as acerola and passion fruit, selecting those with the best yield. These powders were freeze-dried and characterized in terms of physical-chemical parameters and proximate composition, FTIR, TGA and Toxicity. They were then used in the preparation of smoothies, which were also evaluated and characterized. Initial results were obtained during seven-day fermentation, with pH values ​​ranging from 4.5 to 2.49. Acerola scoby powder showed better yield (6.25%) and higher ash content (2.58%) when compared to the others. Regarding acidity, acerola scoby powder had the lowest acidity (3.19 meq.L-1), followed by passion fruit powder (3.77 meq.L-1) and green tea powder (4.15 meq.L-1). For vitamin C content, acerola SCOBY powder presented higher level this compound (1998.04 ± 50.75 mg/100g). The soluble solids content was similar for acerola scoby powder (6.67 ± 0.32 ºBrix) and passion fruit scoby powder (6.13 ± 0.06), being lower than the control scoby powder (8. 13 ± 0.06 ºBrix). The protein content was less than 2% and the water activity was less than 0.3 for all scoby powders evaluated. Regarding microbial counts, lactic acid bacteria counts of 2log and mesophiles of 3log were found. No colonies were detected for the analyzes of acetic bacteria and total yeasts. Acerola, passion fruit and green tea SCOBY powders showed promise, with adequate physicochemical characteristics, significant vitamin C content and microbiological safety. When applying the powders in smoothies, for the rheological analysis of the smoothies, a pseudoplastic behavior was observed, with greater viscosity for the smoothie added with passion fruit powder. When added to smoothies, these powders significantly enriched the nutritional value of the products. Furthermore, FTIR and TG analyzes provided valuable insights into the chemical changes in smoothies due to the addition of SCOBY, enhancing our understanding of their composition and quality. Tests on zebrafish indicated no negative effects on the formulations, while toxicity tests confirmed the safety of the smoothies for human consumption, both pure and diluted. These results open up exciting opportunities in the food industry, offering nutritional and sustainable options to consumers.